Land-use assessment and its influence on spatial distribution of rainfall erosivity: Case study of Cameron Highlands Malaysia - Ul Mustafa, M.R. (2019)
Over the years, Cameron Highlands have witnessed extensive land-use and land-cover (LULC) changes due to the massive agricultural and urbanization activities. This significantly contributed to the erosion problems in the area. Rainfall erosivity that measures the aggressiveness of raindrop in triggering soil erosion is one of its major components that could be influenced by the LULC changes in watersheds. However, the research relating to theLULC changes with the erosivity especially in the complex landscape is scarce. Hence, this study applies geographic information system (GIS) and remote sensing techniques to assess the LULC changes and their influence on the rainfall erosivity distribution in mountainous watershed of Cameron Highlands. Four Landsat images and the rainfall data from the period of thirty years were analysed for the development of LULC and erosivity maps respectively in ArcGIS environment. The study showed that the study area experienced immense land-use changes especially in agriculture and urbanization which affected the erosivity distribution. The LULC change for agriculture increased linearly in the last 30 years from 7.9 in 1986 to almost 16.4 in 2016. The results showed that urban development increased from 5.1 in 1986 to 11.4 in 2016. The increasing urbanization trend was targeted to meet up with tourism requirement in Cameron Highlands. However, forest class declined tremendously due to the exploration of land for agriculture practice and other various types of development. Watershed managers and other stakeholders should find this study beneficial in tackling erosion and its associated ecological challenges. Â© 2018, Polish Society of Ecological Engineering (PTIE).